When mothers kill: interviews from prison - Oberman, Michelle (New York University Press, 2008)
The saddest stories -- She's the world to me : the mother-daughter relationships described by mothers who committed filicide -- Fighting for love : filicidal mothers and their male partners -- Mothering : hopes, expectations and realities -- Punishment, shame and guilt -- Interactions with the state : holes in the safety nets -- The end of the story